Indeks Masa Tubuh pada Antropometri Berat Badan, Tinggi Badan Bagi Anak SMK Batik Sakti 2 Kebumen - Puput Widodo; Diah Nur'Aeni (Departement of Mathematics Education, 2024)
This research consisted of 30 students, namely class X with 20 students and XII with 10 students at SMK Batik Sakti 2 Kebumen. The way to determine normal, obese and thin students is by using the Body Mass Index (BMI). This BMI measurement only requires 2 things, namely height and weight. This study used qualitative research methods. Research requires techniques used by researchers to collect data information and supporting facts in the field for research purposes such as observation, interviews, documentation. Data collection for this research was by carrying out anthropometric measurements. Then the Body Mass Index is measured and broken down based on nutritional status.